Indonesia’s Diplomatic Efforts in WTO Reform after the 13th Ministerial Conference - Zainur Ridho; Arie Kusuma Paksi (Indonesian Perspective, 2026)
Structural stagnation in the World Trade Organization (WTO), such as the paralysis of the Appellate Body and inequality in subsidies and special treatment (S&DT) issues, has encouraged developing countries to demand more inclusive institutional changes. For Indonesia, this stagnation potentially threatens national interests in strategic sectors such as agriculture and fisheries. This study aims to analyze Indonesia's diplomatic strategy as a middle power in encouraging the transformation of the multilateral trading system after the 13th Ministerial Conference (MC13). Using a qualitative-descriptive approach through a single case study and thematic analysis of policy documents, this study found that Indonesia implemented multitrack diplomacy involving the Global South coalition (G33 and LMDC), normative advocacy, and a deliberative approach in multilateral negotiations. As a result, Indonesia managed to secure subsidy exemptions for small-scale fishers, push the principle of capacity-sensitive adjudication in the dispute settlement agenda, and defend the expansion of S&DT coverage. Theoretically, these findings strengthen the concept of middle power diplomacy by demonstrating the effectiveness of normative strategies in the face of global power asymmetry. This study recommends strengthening technical capacity and coordination among domestic institutions to support the consistency and sustainability of Indonesia's diplomatic position in international trade forums.